Effect Of Calcium Nitrate And Gibberellic Acid On Storage Life Of Pear (Pyrus Pyrifolia) Cv. Nijisseiki (Applied Biological Research, 2017)
Fruits of pear (Pyrus pyrifolia) cv. Nijisseiki are vulnerable to post-harvest losses  as its maturity time in north India coincides with summer months. Hence, to  improve the storage life, the fruits were given post-harvest dip of calcium nitrate  @ 0, 2, 3 and 4% and gibberellic acid (GA3) @ 0, 20, 40 and 60 ppm for 5 min.  Treated and untreated (control) fruits were packed in CFB boxes and stored at  low temperature conditions (0-1oC and 90-95% R.H) for 70 days. Fruits were  analyzed for various physicochemical changes on 0, 30, 50 and 70 days after  storage. Both calcium nitrate and GA3 treatments were effective in minimizing the physiological loss in weight (PLW) and maintaining the fruit firmness, total  soluble solids (TSS), titratable acidity, total sugars content, sensory quality and  pectin methyl esterase (PME) activity as compared to control during storage  period. After 70 days of storage, minimum PLW (4.81%) and highest fruit  firmness (3.88 kgf), sensory quality (7.15), TSS (12.35%) total sugars (8.45%),  and PME activity (1.31 ml of 0.02 N NaOH used) were recorded in 3% calcium  nitrate treated fruits.
Keywords: Calcium nitrate; fruit quality; gibberellic acid; pear; storage